Critical Thinking of Field Independent Students; which Model of Teaching is more Supportive? - Nurnia Nurnia; Herlina Anggaraini Tasina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2020)
This study examines whether a certain learning condition as of model of teaching is more supportive to the enhancement of critical thinking of field independent students. To be brief is that whether students with cognitive style of field independent function more superior through particular implemented models of flipped classroom, pure online or direct instruction. The study was a quasi-experiment conducted to 96 English majors divided equally in three different classes and treated with a different model. Data were collected by asking samples to take a critical thinking skills test after the treatment. Data were analyzed by means of two-way analysis of variance. Findings of the study show that the critical thinking skills of field independent students differ significantly after the three models implementation and the flipped classroom model is found to be more supportive.